Reasoning Words as Linguistic Features of Exploratory Talk: Classroom Use and What It Can Tell Us. Issue 1 (2nd January 2017) - Boyd, Maureen; Kong, Yiren
Abstract : Reasoning words are linguistic features associated with classroom exploratory talk as students talk-to-learn, explore ideas, and probe each other's thinking. This study extends established research on use of reasoning words to a fourth- to fifth-grade literature-based English language learning context. We examined frequency and patterning of teacher and student use of reasoning words within and across two lessons purposefully selected to elucidate use of reasoning words during a close reading of a text as students grapple to make meaning and extended intertextual talk about a text that is easily accessible. Analyses and exemplifications illuminate how usage of each reasoning word functioned to introduce/link to reasoning or to prompt for reasoning. Teacher used reasoning words to mostly prompt for reasoning and student used them to introduce/link to reasoning. We found consistent use of reasoning words by teacher and students across three categories: language of possibility, reasoning links, and pressing for reasoning.